Pengaruh Pendampingan Keluarga terhadap Manajemen Cairan pada Pasien Hemodialisa: Literature Review - Agus Susilawati; Hema Malini; Reni Prima Gusty (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The role of the family in hemodialysis patients is very helpful in encouraging individual health in carrying out fluid management. A good or very active family role will further enhance the patient's enthusiasm for managing fluid management. Much research has been done on fluid management, but it only involves the patient, not the patient's family. The research method used is literature review by identifying journal articles published online consisting of English and Indonesian in 2018-2022. Articles were retrieved using search engine tools PubMed, Science Direct, and Google Scholar. There are 7 journals based on inclusion criteria. The results showed that there was an effect of family assistance on fluid management in hemodialysis patients.